Technological Revolutions, Innovations, and Trade Performance - Jakob B. Madsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
This paper addresses two puzzles in international trade, namely why traditional estimates of income elasticities of exports are implausibly high and why the export growth varies much more markedly across countries than can be explained by price competitiveness and variations in income in export markets. Using data for 18 OECD countries it is shown that integration, the level of technology and the technological competitive position can, to a large degree, explain these two puzzles.
Keywords: F10; O30; 330; technology; external patents; product variety; trade; ICT revolution; Einkommenselastizität; Technischer Fortschritt; Patent; Produktdifferenzierung; Außenhandel; Schätzung; OECD-Staaten